ANALISIS PENYEBAB KETERLAMBATAN VERIFIKASI KLAIM BPJS PADA PEMBIAYAAN PASIEN DI RUMAH SAKIT UMUM MITRA PARAMEDIKA: ANALISIS PENYEBAB KETERLAMBATAN VERIFIKASI KLAIM BPJS PADA PEMBIAYAAN PASIEN DI RUMAH SAKIT UMUM MITRA PARAMEDIKA - R. Haryo Nugroho P; Wahyu Joko Pamungkas (Jurnal Permata Indonesia, 2022)
Background : Mitra Paramedika hospital is a type D hospital which is about 84-86% is include BPJS pasien, event BPJS PBI and Non PBI in the BPJS claim process has som issues, where is make the BPJS claim verification is be delayed. Claim submission that should have been mad on the 10 th of the following moth to be later than the 13 th can only be submitted for BPJS claims. Because there is has an impact for hospital income. From this background the researcher wants to know whats is the factors are be come causes BPJS claim verification to experience delay. Purpose : wants to know whats is the factors are become causes of BPJS claim verification to experience delay. Method : The research used is descriptive analitatif research with case study research design. Results : From this research shows thet the delay from BPJS claim verification based on method, material, man, machine, measurement, and environment. On the method factor the wholt officers is understand and know the BPJS health claim flow. On the material factors there is lack and incomplete one the file. On the man factor there is a miscommunication between helth care worker. On the machine factor, on BPJS claim prosses used the new version of INA-CBGs application. On the measurement factor there is doesn’t have SOP about BPJS claim and just using MoU also minister of health of republic Indonesian regulations as regulation to used. On the environment factor, the work environment affect the work comfort of officers in do their job, but there is not being the factor of BPJS health claim verification. Conclusion : The inhibiting factors in BPJS Health claims verification is from the material (there is lack and incomplate of filling the file), from the man factors (there is a miscommunication between health care workers), from the measurement factors (there is doesn’t have SOP about BPJS claim). Keywords : BPJS health claim delay, claim delay factor, delay factor effect